Sur l'état de la végétation algale macrophyte du littoral roumain de la mer noire, pendant la période estivale de l'année 1977 - Celan, Maria; Bavaru, Adrian; Bologa, Alexandru S. (Cercetări Marine - Recherches Marines, 2026)
The paper presents data regarding to the state of the Romanian Black Sea coast macrophyte algae vegetation in the 1977 summer period. Are ascertaining a resolute influence which had the belt Cyetoseira disappearance on the algae vegetation evolution. The total or near total disappearance of a great number of species was established, in the first line Laurencia. Species of the Geranium genus arrived to impress a peculiar physiognomy to the algae vegetation.